The effect of foreign investment, domestic capital investment, sharia investment, and population as drivers of Indonesia's economic growth - Primastuty, Pinny; Harahap, Isnaini; Harahap, Muhammad Ikhsan (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
Economic development improves human resources, public welfare, and national equality. Investment sustains economic development. According to the Harrod-Domar hypothesis, investment increases productivity and economic development. This research seeks to confirm this. The researcher also adopts Umar Chapra's ideas. His views combine Islam with morals to build a healthy economy. Using quantitative methods, this study includes FDI, domestic investment, Islamic investment, population, and GDP as fundamental and related variables. The analysis found that FDI and DCI are the independent variables affecting Indonesia's economic progress. Building a company requires much cash, so Indonesia needs both to strengthen its economy. Islamic investment is still low, and Indonesia's large population has not been well controlled, causing unemployment, low education levels, many health problems, and other problems that hinder economic growth. Public interest statements This analysis found that FDI and DCI are the independent variables affecting Indonesia's economic progress. Building a firm requires a lot of cash, so Indonesia needs both to strengthen its economy. Islamic investment is still low, and Indonesia's large population has not been properly controlled, causing unemployment, low education levels, many health problems, and others that hinder economic growth. Note: Early Version articles are published as standalone pieces and will later be compiled into issues prior to print publication. These Early Version articles will not appear in journal keyword searches, will not be included in article searches, and will not receive a DOI (Digital Object Identifier) until they are officially published in an issue.